2020
DOI: 10.1016/j.nicl.2019.102142
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of rumination in major depressive disorder: A brain network analysis

Abstract: HighlightsWe employed a high-field 7-T functional MRI data-driven graph-theory approach.Higher rumination was associated with reduced precuneus strength in depression.Higher rumination related to lower MOFC influence on the precuneus in depression.Overall rumination related to lower connectivity within the DMN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 72 publications
(97 reference statements)
0
41
0
1
Order By: Relevance
“…The precuneus, which is functionally divided into several regions, contributes to multiple networks and it is involved in a variety of cognitive processes including, but not limited to, visuospatial processing, episodic memory, and self-referential processes. In this context, investigating the dynamic configurations connecting the precuneus with other regions cannot be captured from a static perspective of FC, such as in Jacob et al (2020) , which ignores changes that might occur in the temporal domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precuneus, which is functionally divided into several regions, contributes to multiple networks and it is involved in a variety of cognitive processes including, but not limited to, visuospatial processing, episodic memory, and self-referential processes. In this context, investigating the dynamic configurations connecting the precuneus with other regions cannot be captured from a static perspective of FC, such as in Jacob et al (2020) , which ignores changes that might occur in the temporal domain.…”
Section: Discussionmentioning
confidence: 99%
“…The links in this brain subsystem were mainly long-distance correlations between regions of the DM network and regions outside the DM network, with the right precuneus accounting for the largest number of them. The precuneus, as a core component of the DM network (Utevsky et al, 2014 but see also Margulies et al, 2009) may be important for self-referential processing (Fransson and Marrelec, 2008;Van Buuren et al, 2010) and has been commonly described with aberrant resting-state activity (Liu C.-H. et al, 2017;Li et al, 2018) and connectivity in patients with depression (Zhu et al, 2012;Dutta et al, 2019;Jacob et al, 2020). The study by Jacob et al (2020) found reduced strength connectivity of this region to be linked to higher rumination tendency (i.e., an exaggerated focus on negative thoughts) in patients with depression.…”
Section: The Precuneus Accounts For the Overall Reduced Static Fc Inmentioning
confidence: 99%
“…Thus, rodent studies using systematic activity mapping after acute and chronic stress have been useful to understand functional consequences of stress-related pathology. For example, functional magnetic resonance imaging (fMRI) studies in CRS mice identified dendritic remodeling of the PFC, HPC, and amygdala with altered functional connectivity across regions of the default mode network 39 , in which activity changes are linked to symptom emergence in MDD 40 , PTSD 41 , Parkinson's disease 42 , and substance abuse disorders 43 . Immediate early gene (IEG) markers, such as c-Fos, similarly yield high spatiotemporal resolution for characterizing functional alterations induced by chronic stress.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al 23 found decreased connectivity of the precuneus to the DMN in patients with MDD compared to HCs. In addition, a recent fMRI study found that reduced strength of the right precuneus was associated with higher maladaptive rumination levels in patients with MDD 64 . Among the few studies directly comparing both BD and MDD patients, Liang et al 65 found that the regional homogeneity value of the precuneus was increased in BD and MDD patients.…”
Section: Discussionmentioning
confidence: 99%